2017
DOI: 10.1186/s13039-017-0308-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of the 22q11.2 deletion in a large cohort of miscarriage samples

Abstract: BackgroundThe 22q11.2 deletion syndrome is the most common microdeletion syndrome in livebirths, but data regarding its incidence in other populations is limited and also include ascertainment bias. This study was designed to determine the incidence of the 22q11.2 deletion in miscarriage samples sent for clinical molecular cytogenetic testing.ResultsTwenty-six thousand one hundred one fresh product of conception (POC) samples were sent to a CLIA- certified, CAP-accredited laboratory from April 2010–-May 2016 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Second, prenatal cases with ultrasound anomalies are more likely to be terminated. Finally, 22q11.2 pregnancies are thought to be more prone to end in a miscarriage: in a recent study in which the incidence of 22q11.2 deletions in 26 101 products of conception was examined, 21 12/9398 (0.13%) samples that were normal at karyotype resolution had an isolated 22q11.2 deletion, approaching the prevalence in our prenatal population. Of our 41 cases, 53.7% had an ultrasound anomaly that was clearly related to the genetic finding.…”
Section: Discussionmentioning
confidence: 58%
“…Second, prenatal cases with ultrasound anomalies are more likely to be terminated. Finally, 22q11.2 pregnancies are thought to be more prone to end in a miscarriage: in a recent study in which the incidence of 22q11.2 deletions in 26 101 products of conception was examined, 21 12/9398 (0.13%) samples that were normal at karyotype resolution had an isolated 22q11.2 deletion, approaching the prevalence in our prenatal population. Of our 41 cases, 53.7% had an ultrasound anomaly that was clearly related to the genetic finding.…”
Section: Discussionmentioning
confidence: 58%
“…The prevalence is similar in miscarriages and products of conception . This differs from the prevalence in an unselected cohort of neonates, which was found to be 1/3672 in a retrospective analysis of dried newborn bloodspots using microarray technology (CVS/AF vs neonates: OR 4.4821, 95% CI, 1.7370‐11.5655; POCs vs neonates: OR 3.6356, 95% CI, 1.5370‐8.5994)…”
Section: Introductionmentioning
confidence: 81%
“…OMA detected three pCNV of a deletion at 22q11.2, a deletion at 18q23, and a deletion at Xp22.33p22.31. A study of 22,451 miscarriage samples reported a higher incidence of 22q11.2 deletion in the miscarriages than the reported prevalence in the general population, indicating that the 22q11.2 deletion could be a causal factor for miscarriage [ 17 ]. Deletions of the distal region of 18q are associated with chromosome 18q deletion syndrome with wide phenotypic variability [ 18 ].…”
Section: Discussionmentioning
confidence: 99%